Property taxation and real estate investment in Perú - Acosta Bernedo, Otto Alonso (2016)
In the present article, the authors analyze the issues related to the Property Taxation on venues that have urban habilitation and/or buildingprojects.In order to accomplish that, the authors examine the basis of the right to build, describe the stages of the constructive administrative procedure as regulated in Law 29090 and, finally, comment on the recent precedent of the Tax Court whichregards the matter.